Anoikis in phenotypic reprogramming of the prostate tumor microenvironment - Nepali, Prerna R.; Kyprianou, Natasha (Frontiers in Endocrinology, 2023)
Prostate cancer is one of the most common malignancies in males wherein 1 in 8 men are diagnosed with this disease in their lifetime. The urgency to find novel therapeutic interventions is associated with high treatment resistance and mortality rates associated with castration-resistant prostate cancer. Anoikis is an apoptotic phenomenon for normal epithelial or endothelial cells that have lost their attachment to the extracellular matrix (ECM). Tumor cells that lose their connection to the ECM can die via apoptosis or survive via anoikis resistance and thus escaping to distant organs for metastatic progression. This review discusses the recent advances made in our understanding of the signaling effectors of anoikis in prostate cancer and the approaches to translate these mechanistic insights into therapeutic benefits for reducing lethal disease outcomes (by overcoming anoikis resistance). The prostate tumor microenvironment is a highly dynamic landscape wherein the balance between androgen signaling, cell lineage changes, epithelial-mesenchymal transition (EMT), extracellular matrix interactions, actin cytoskeleton remodeling as well as metabolic changes, confer anoikis resistance and metastatic spread. Thus, these mechanisms also offer unique molecular treatment signatures, exploitation of which can prime prostate tumors to anoikis induction with a high translational significance.